2008
DOI: 10.1063/1.2875617
|View full text |Cite
|
Sign up to set email alerts
|

Probing the duplex stainless steel phases via magnetic force microscopy

Abstract: Duplex stainless steels are austenitic-ferritic alloys used in many applications, thanks to their excellent mechanical properties and high corrosion resistance. In this work, chemical analyses, x-ray diffraction, and magnetic force microscopy (MFM) were employed to characterize the solution annealed and aged duplex stainless steel. The samples exhibited no changes in lattice parameters and the MFM technique proved successful in clearly imaging the magnetic domain structure of the ferrite phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
1
6
0
2
Order By: Relevance
“…As ferrite is ferromagnetic, and austenite and sigma phase are paramagnetic [15,16], it is possible to use this magnetic interaction to differentiate between the phases. The technique has previously been used to undertake an analysis of the magnetic properties of the ferrite bands in duplex steels [17][18][19], however, these workers have not used the technique to characterise the distribution and volume fraction of various phases in the overall microstructure. Recently, Warren et al [20] have compared EBSD with MFM for the quantification of ferrite in Type 321 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…As ferrite is ferromagnetic, and austenite and sigma phase are paramagnetic [15,16], it is possible to use this magnetic interaction to differentiate between the phases. The technique has previously been used to undertake an analysis of the magnetic properties of the ferrite bands in duplex steels [17][18][19], however, these workers have not used the technique to characterise the distribution and volume fraction of various phases in the overall microstructure. Recently, Warren et al [20] have compared EBSD with MFM for the quantification of ferrite in Type 321 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…MFM imaging is also carried out successfully on alloyed and unalloyed ferritic and/or dual phase stainless steels (DSS) as an alternative technique compared to destructive techniques such as chemical etching [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…So far, it sounds like that no characterisation of the magnetic domain structures of DSSs after different thermal and mechanical treatments has been performed (except for the preliminary result from Gheno et al [10]). The present work reports on the magnetic domain structures of the DSS, 7MoPLUS, after solution treatment at different temperatures, spinodal decomposition, and plastic deformation.…”
Section: Introductionmentioning
confidence: 97%
“…Later on, several groups of authors showed the convenience of using MFM for phase identification of DSSs without much sample preparation [9][10][11]. One of the groups (Gheno et al [10]) also reported preliminarily on the change in magnetic domain structure in a DSS attendant to spinodal decomposition.…”
Section: Introductionmentioning
confidence: 97%